Handling Classrooms with Students having Heterogeneous Learning Abilities - Aluvalu, Rajani Kanth; Kulkarni, Vivek; Asif, Md. (Journal of Engineering Education Transformations, 2017)
Classrooms in educational institutions consist of students with varying learning abilities. Faculty delivering a lecture in a uniform pitch in such classrooms will fail to teach and reach the learning levels of heterogeneous student groups. In every classroom, the faculty members deliberately experience low, medium, and high learners/readers as measured by assessments. In fact, it is biggest challenge faculties are facing to overcome. Faculty following traditional teaching techniques fails to achieve optimized classroom audibility levels and optimize the students learning in the classroom.With faculty's uniform approach to teaching, the learning needs of individual students may not be fully met in heterogeneous classroom environments.The teaching strategies followed to optimize the learning of heterogeneous students with experimental results and handling such classrooms are discussed in this paper. This study will help faculties wishing to improve the quality and effectiveness of teaching and learning in heterogeneous classrooms.